Spatial Diffusion of Civil Liberty - Chasco, Coro (2021)
This paper studies the existence of spatial diffusion of civil liberty among neighboring countries. For that purpose, we first combine different exploratory space-time data analysis approaches to find that this phenomenon is spatially clustered and that a convergence process is at work among the world countries from 1985 to 2010, with a structural change by the end of the Twentieth century mainly due to the appearance of the Internet. Second, we specify a spatial autoregressive panel data model for a sample of 130 countries, for 1985–2000, and 172 countries, for 2000–2010. Results provide evidence for spatial diffusion of civil liberty, though it is not constant along this time span. The spreading rate is 0.34 in the first sub-period. After 2000, it reduces to 0.21; that is, countries only “catch” 21% of the average changes in their neighbors’ civil liberty levels. Additionally, religious culture, urban agglomeration and GDP explain the levels of civil liberties in the world.